EKSPLOITASI SUMBER DAYA ALAM HUTAN SEBAGAI INSPIRASI DALAM BERKARYA SENI LUKIS - MURDIANA, Ir. Drs. Heldi, M.Si, Drs. Mediagus (Serupa The Journal of Art Education, 2014)
The purpose of this thesis is (1) to provide enlightenment, visualizing works of art to the public about the importance of forest conservation are many benefits for life. (2) Exploitation of forests in Indonesia are still happening. Illegal logging, forest fires and land conversion, giving rise to a variety of natural disasters. The method of painting creation through small sketches on paper and canvas media translated into human behavior with display objects to the natural environment, with staining techniques that highlight the bright colors, as well as the creator's imagination combines with the elements and principles of art thus reflected the originality of viewpoint and style ideas with the creators of post-impressionis.Keywords: Exploitation, Forest, Art, Post-impressionis